The Impact of the Eurozone Crisis on Turkish Foreign Trade - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
The aim of this paper is to search for the impact of the Eurozone Crisis on Turkish foreign trade. To that end, panel data analysis is used for 15 Eurozone members and for the period of 1995-2011. The main finding of the empirical study is that private sector debt of the Eurozone states has a negative relationship with Turkish trade balance. This paper also presents the establishment of a monitoring mechanisms related to trade and debt and close cooperation of Turkish governmental institutions with EU authorities as policy recommendations.